The Drosophila kinesin-like protein KLP3A is required for proper behavior of male and female pronuclei at fertilization. - Williams, B.C.; Dernburg, A.F.; Puro, J.; Nokkala, S.; Goldberg, M.L. (Development, 1997)
Drosophila melanogaster females homozygous for mutations in the gene encoding the kinesin-like protein KLP3A are sterile (Williams et al., 1995). We have investigated the basis of this sterility. The eggs produced by KLP3A mutant mothers are fertilized by sperm, and female meiosis appears to occur normally. However, the large majority of these embryos arrest their development soon thereafter with a characteristic phenotype. The four nuclei produced by female meiosis associate together in a polar body-like structure, while a bipolar spindle is established around the metaphase-arrested male pronucleus. Thus, the major defect caused by depletion of the KLP3A protein is either in specification of the female pronucleus, or in migration of the male and female pronuclei toward each other. We have also found that the KLP3A protein is located throughout the metaphase spindle during meiosis and the early embryonic mitotic divisions, but later accumulates specifically at the midzone of these same spindles during telophase. The protein is also present on two other microtubule structures: the sperm aster; and the radial, monastral array of microtubules established between the two meiosis II spindles. We discuss these results in light of possible functions of the KLP3A protein in pronuclear specification and migration.